2018
DOI: 10.1073/pnas.1711490115
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the structural origins of cryptic sites on proteins

Abstract: Molecular dynamics (MD) simulations of proteins reveal the existence of many transient surface pockets; however, the factors determining what small subset of these represent druggable or functionally relevant ligand binding sites, called "cryptic sites," are not understood. Here, we examine multiple X-ray structures for a set of proteins with validated cryptic sites, using the computational hot spot identification tool FTMap. The results show that cryptic sites in ligand-free structures generally have a strong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
162
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(166 citation statements)
references
References 52 publications
4
162
0
Order By: Relevance
“…A single hot spot at the ATP binding site was detected by mapping unbound structures in the DFG-in loop conformation whereas multiple hot spots, that cover both the ATP binding site and the connected sub-pocket, were identified upon mapping a bound structure in the DFGout conformation. 46 Besides, it has been suggested that cryptic binding sites have a strong binding hot spot in the vicinity and exhibit above-average flexibility around the incipient pockets, 46 which coincides with the behavior of the cryptic sub-pocket of p38 MAP kinase.…”
Section: Resultsmentioning
confidence: 85%
“…A single hot spot at the ATP binding site was detected by mapping unbound structures in the DFG-in loop conformation whereas multiple hot spots, that cover both the ATP binding site and the connected sub-pocket, were identified upon mapping a bound structure in the DFGout conformation. 46 Besides, it has been suggested that cryptic binding sites have a strong binding hot spot in the vicinity and exhibit above-average flexibility around the incipient pockets, 46 which coincides with the behavior of the cryptic sub-pocket of p38 MAP kinase.…”
Section: Resultsmentioning
confidence: 85%
“…4b,c). These structures are the ones of ZMYND11 and PB1 (6), BDs that present substantial sequence variation -particularly in the ZA-loop region-compared to the general trend.…”
Section: Resultsmentioning
confidence: 95%
“…The other crystallographic evidence is a structure of PB1 (6), which is also an atypical BD having an unusually short ZA-loop. 20 In comparison with SMARCA2, a member of the same family, it shows a very similar opening despite having a low sequence identity (Figure 4c).…”
Section: Dna-could Also Lead To Such Conformational Changesmentioning
confidence: 99%
See 1 more Smart Citation
“…Retrospective analysis of other validated drug targets suggests cryptic sites created by the movement of secondary structure elements, such as the displacement of helix 7, are often druggable. 40 The potential druggability of this cryptic site is also supported by application of the FTMap algorithm,41,42 which predicts a number of hotspots within the pocket where small molecules could form a variety of energetically-favorable interactions ( Supplementary Fig. 1).…”
Section: Computer Simulations Reveal a Potentially Druggable Cryptic mentioning
confidence: 97%